2014
DOI: 10.1371/journal.pone.0102982
|View full text |Cite
|
Sign up to set email alerts
|

Can Occupancy–Abundance Models Be Used to Monitor Wolf Abundance?

Abstract: Estimating the abundance of wild carnivores is of foremost importance for conservation and management. However, given their elusive habits, direct observations of these animals are difficult to obtain, so abundance is more commonly estimated from sign surveys or radio-marked individuals. These methods can be costly and difficult, particularly in large areas with heavy forest cover. As an alternative, recent research has suggested that wolf abundance can be estimated from occupancy–abundance curves derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The average wolves’ territory size vary between 100 and 400 km² in western and central Europe (Ciucci et al , Mech and Boitani , Duchamp et al ). Although these cells might not entirely cover wolves territories, Latham et al () studied the effect of grid size to assess wolf's occupancy and found that taking a large grid size may not be appropriate for areas with moderate to high wolf density as it can overestimate occupancy rate. On the other hand, if the size of the sampling unit is too small, then there is a risk of having very few detections within a year, which would make the estimation of the detection probability difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The average wolves’ territory size vary between 100 and 400 km² in western and central Europe (Ciucci et al , Mech and Boitani , Duchamp et al ). Although these cells might not entirely cover wolves territories, Latham et al () studied the effect of grid size to assess wolf's occupancy and found that taking a large grid size may not be appropriate for areas with moderate to high wolf density as it can overestimate occupancy rate. On the other hand, if the size of the sampling unit is too small, then there is a risk of having very few detections within a year, which would make the estimation of the detection probability difficult.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the relationship between wolf ( Canis lupus ) occupancy and density is curved and, furthermore, the curvature depends on sampling grid size (Latham et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, understanding and monitoring the expansion of the grey wolf’s range is important for preventing or mitigating conflicts as well as for conservation and management purposes. However, the monitoring of wolves is still challenging in the field because it is a wide-ranging habitat generalist, which lives at low densities and is often secretive and elusive [ 18 , 19 ]. Moreover, the conventional methods used for detecting the presence of grey wolves and estimating their number and population dynamics can be very time-consuming and costly.…”
Section: Introductionmentioning
confidence: 99%